2008
DOI: 10.1111/j.1524-4725.2008.34284.x
|View full text |Cite
|
Sign up to set email alerts
|

Second-Generation 1,550-nm Fractional Photothermolysis for the Treatment of Acne Scars

Abstract: Fractional photothermolysis is a safe and efficacious treatment modality for the treatment of all types of acne scars of all severities. No adverse effects were noted, including in patients with Fitzpatrick Skin Types III to V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 21 publications
2
36
0
1
Order By: Relevance
“…The percentage of subjects with skin types IV and V included in studies for the treatment of atrophic scarring are very limited compared to lighter skin types due to pigmentation concerns [1][2][3]. Even with the use of hydroquinone pre-and post-treatment, a recently published prospective study of 15 subjects with skin types IV-VI and acne scarring using Erbium-doped YAG laser showed a 50% rate of the PIH [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of subjects with skin types IV and V included in studies for the treatment of atrophic scarring are very limited compared to lighter skin types due to pigmentation concerns [1][2][3]. Even with the use of hydroquinone pre-and post-treatment, a recently published prospective study of 15 subjects with skin types IV-VI and acne scarring using Erbium-doped YAG laser showed a 50% rate of the PIH [12].…”
Section: Discussionmentioning
confidence: 99%
“…Current methods of treating scarring include traditional fully ablative erbium and carbon dioxide (CO 2 ) treatments as well as non-ablative and ablative fractional resurfacing with CO 2 , erbium:yttrium-aluminum-garnet (Er:YAG), and erbium:yttrium-scandium-galium-garnet (Er:YSGG) lasers [1][2][3][4][5][6][7][8]. These options can be challenging for skin type IV patients and not feasible for patients with skin types V-VI without significant pre-and post-treatment skin conditioning and a hyper-pigmentation risk.…”
mentioning
confidence: 99%
“…Previous experiences with fractional photothermolysis in treating acne scarring have demonstrated its effectiveness [5,6]. In our clinic, we have used fractional photothermolysis with good clinical outcomes in the treatment of acne scars.…”
Section: Introductionmentioning
confidence: 96%
“…In 2 studies investigating the efficacy of EDL in acne scarring with 2 to 6 monthly treatments (82 patients, skin types I-V), 62% to 87% of patients experienced a 51% to 75% scar improvement. 48,49 The average improvement increased proportionally after each treatment and did not significantly differ depending on skin type. 48 More recent studies have confirmed the laser's safety and efficacy in treating acne scarring, even in darker skin types.…”
Section: Acne Scarringmentioning
confidence: 92%